Invisible hands, indelible impact: Women social workers in Acehs disaster recovery - Putri Saleh; Alfi Rahman; Ezri Hayat; Rizanna Rosemary (International Journal of Disaster Management, 2025)
This study examines the critical but often underrecognized roles of women social workers in the context of post-tsunami disaster recovery and resilience-building in Aceh, Indonesia. Drawing on twenty in-depth interviews and a focus group discussion with certified social workers, community volunteers, journalists, academics, and activists, the research explores how women navigate cultural, institutional, and professional barriers during disaster response and recovery. Guided by feminist disaster theory, intersectionality, and transformative social work frameworks, the analysis reveals that women not only provide essential care labor and psychosocial support but also act as agents of changeinitiating community-based projects, advocating for gender-sensitive policies, and building informal support networks. Despite persistent patriarchal norms and limited institutional recognition, women social workers demonstrate remarkable agency, adaptability, and collective resilience. The findings highlight the urgent need for gender-inclusive policies, improved professional pathways, and greater institutional support to empower women as leaders in disaster management. This research contributes to a more nuanced understanding of gender, power, and professional practice in humanitarian contexts, offering insights for both policy and practice in Indonesia and similar settings.